ASEAN ECONOMIC INTEGRATION: TRADE CREATION OR TRADE DIVERSION FOR IMPORT OF INDONESIA MANUFACTURES? - Saleh, Samsubar; Suprayitno, Bambang (Economic Journal of Emerging Markets, 2011)
This research investigates the trade creation and trade diversion of Indonesia manufactures import from extra and intra ASEAN countries after ASEAN economic integration. Using regression analysis, the study suggests that Indonesia manufactures import has been diverted from extra ASEAN countries both in short run and long run. In the short run, the ASEAN economic integration does not result in trade creation for Indonesia manufactures import from intra-ASEAN countries. This might stems from the insignificant difference Common Effective Preferential Tariff (CEPT) and Most Favoured Nation (MFN) tariffs and the existence of non-tariff barriers. Keywords: Economic integration, trade creation, trade diversion, Indonesia manufactures JEL classification numbers: F15, O14